2010
DOI: 10.1007/s10534-010-9334-0
|View full text |Cite
|
Sign up to set email alerts
|

Testicular toxicity induced by dietary cadmium in cocks and ameliorative effect by selenium

Abstract: Cadmium (Cd) is an ubiquitous environmental pollutant that has been associated with male reproductive toxicity in animal models. However, little is known about the reproductive toxicity of Cd in birds. To investigate the toxicity of Cd on male reproduction in birds and the protective effects of selenium (Se) against subchronic exposure to dietary Cd, 100-day-old cocks received either Se (as 10 mg Na(2)SeO(3) per kg of diet), Cd (as 150 mg CdCl(2) per kg of diet) or Cd + Se in their diets for 60 days. Histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 52 publications
1
67
0
1
Order By: Relevance
“…However, basopenia has been reported in association with stress-and druginduced reactions and autoimmune diseases (Grattan et al, 2003), but further research is indispensable to clarify the results of the present study. Other studies with concurrent Cd and inorganic Se addition in feed or drinking water showed that although Se could not counteract for Cd-induced decreased performance it improved other examined parameters such as tissue structural damages, antioxidant defence and apoptosis (Jihen et al, 2008;Li et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, basopenia has been reported in association with stress-and druginduced reactions and autoimmune diseases (Grattan et al, 2003), but further research is indispensable to clarify the results of the present study. Other studies with concurrent Cd and inorganic Se addition in feed or drinking water showed that although Se could not counteract for Cd-induced decreased performance it improved other examined parameters such as tissue structural damages, antioxidant defence and apoptosis (Jihen et al, 2008;Li et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors reported that intraperitoneal Cd administration (0.32 to 1.62 mg/kg BW) to hens did not cause negative effects on BW, feed intake and haematocrit but reduced egg production. In another study by Li et al (2010b), cocks were fed a diet with 10 mg/kg of inorganic Se or 150 mg/kg of Cd or a combination of those levels. The authors reported reduced final BW in the Cd group compared with the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of cadmium to chickens decreased SOD activities in various tissues, including liver [137][138], kidney [139], blood [140], ovary [141], testes [142] and splenic lymphocytes in vitro [143]. Usually, decreased SOD activity was accompanied by decreased GSH-Px activity and increased lipid peroxidation in the same tissues.…”
Section: Toxicological Stressesmentioning
confidence: 98%
“…Grotto et al [39] reported that in rats chronically exposed to low levels of methylmercury, selenium co-administration showed a significant reduction in methylmercury-induced genotoxicity, reestablished glutathione peroxidase activity and reduced and Histochemical Alterations in Prostate of Albino Rats DNA damage. Selenium reduced the cadmium induced histopathological changes in testes of rat, oxidative stress, endocrine disorder and apoptosis [40,41]. On the contrary, Adesiyan et al [42] reported that selenium had no protective effects against atrazine-induced biochemical alterations in testis and epididymis except testicular lactate dehydrogenase.…”
Section: Figurementioning
confidence: 99%